VGLUT2 may improve cognitive function in depressed rats by protecting prefrontal cortex neurons - Liu, Longfei; Hu, Yongxue; Shan, Qing; Li, Peifan; Ma, Tianpei; Wang, Yiming (Frontiers in Behavioral Neuroscience, 2024)
Objective: Depression may be accompanied by cognitive impairment, but its pathogenesis remains unclear. This study aims to investigate the protective effects of fluoxetine on behavioral performance and prefrontal cortex neuronal damage in rats with depression-associated cognitive impairment, based on the observation of VGLUT2 protein expression. Methods: Forty-five SPF-grade male SD rats were randomly divided into three groups (n=15): normal control group (CON), depression group (DD), and fluoxetine group (DD+F). The CON group was reared normally, while the DD and DD+F groups underwent chronic unpredictable mild stress (CUMS) combined with social isolation to induce a depression-related cognitive dysfunction model. After modeling, the DD+F group was treated with fluoxetine (10mg/kg, ig) for 14 days. Behavioral tests were performed to assess changes in mood, cognition, learning, and social abilities. Histopathological observations were made to examine pathological changes, neuronal apoptosis, ultrastructure, and dendritic spine density in the prefrontal cortex. The concentration, relative expression level, and mRNA expression of VGLUT2 protein were also measured. Finally, a correlation analysis was performed between the relative expression level and mRNA expression of VGLUT2 protein and the pathological changes in neurons. Results: Compared to the CON group, the DD group exhibited decreased body weight, anhedonia, increased behavioral despair, reduced locomotor activity and spontaneous exploratory behavior, impaired spatial learning and memory, and decreased social interaction and social cognitive ability. Pathological damage was observed in the prefrontal cortex, with neuronal apoptosis, ultrastructural damage, and reduced neuroplasticity. The concentration, relative expression, and mRNA expression levels of VGLUT2 protein were decreased. Following fluoxetine intervention, the above behavioral phenotypes improved; pathological damage showed varying degrees of recovery; and the concentration, relative expression, and mRNA expression levels of VGLUT2 protein increased. Finally, there was a significant correlation between VGLUT2 protein expression and pathological changes in the prefrontal cortex. Conclusion: After 28 days of CUMS combined with isolation rearing, rats exhibited impairments in mood, cognition, learning, and social abilities, with neuronal damage and decreased VGLUT2 protein levels in the prefrontal cortex. Following fluoxetine intervention, VGLUT2 protein expression increased, neuronal repair in the prefrontal cortex occurred, depressive-like behavior improved, and cognitive learning and social abilities were restored.